2017
DOI: 10.1007/s12574-017-0362-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between plasma brain natriuretic peptide levels and left atrial appendage flow velocity in patients with non-valvular atrial fibrillation and normal left ventricular systolic function

Abstract: This study showed that a higher plasma BNP was associated with a lower LAA flow velocity in patients with NV-AF and normal LV systolic function. The plasma BNP may complement the role of the CHADS score in predicting lower LAA flow velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…This can also explain the view that some scholars believe that LAD can predict the risk of stroke[ 32 ]. However, similar to the study of Harada M et al [ 33 ], the multiple linear regression analysis did not prove that LAD is an independent factor of the LAAFV. Therefore, this needs more research to confirm.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This can also explain the view that some scholars believe that LAD can predict the risk of stroke[ 32 ]. However, similar to the study of Harada M et al [ 33 ], the multiple linear regression analysis did not prove that LAD is an independent factor of the LAAFV. Therefore, this needs more research to confirm.…”
Section: Discussionsupporting
confidence: 50%
“…The reason may be that the population included in our study is mainly NVAF patients with normal LVEF. So far, studys on the relationship between LVMI and LAA are rare, and there seems to be some controversy [ 33 , 35 ]. Our study showed that LAAFV was negatively correlated with LVMI, and the multiple linear regression analysis proved that LVMI is an independent factor of the LAAFV, which is similar to the study of Harada M et al [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [ 38 , 39 ] found that elevated BNP was associated with LAA disfunction, and a high plasma brain natriuretic polypeptide level was a marker of risk for thromboembolism in patients with nonvalvular atrial fibrillation [ 40 ]. Harada et al also found that higher plasma BNP was associated with a lower LAA flow velocity in patients with nonvalvular AF and normal LV systolic function [ 17 ]. Therefore, in addition to diagnosing heart failure, the serum level of NT-pro BNP could, to a certain degree, reflect the function of left atrium and left atrial appendage.…”
Section: Discussionmentioning
confidence: 99%
“…Predictors in our model included demographics (age and sex), previous medical history (history of atrial fibrillation, hypertension, heart failure, diabetes, stroke, and vascular diseases), anticoagulant drugs and left atrial (LA) diameter. In addition, many studies have proved the correlation between NT-proBNP and LAA flow velocity [ 15 , 16 , 17 ]. Therefore, we chose BNP as one of the predictors.…”
Section: Methodsmentioning
confidence: 99%
“…When atrial fibrillation occurs, the left atrium cannot contract effectively, the damage of left ventricular diastolic function and the increase of left ventricular filling pressure can lead to left atrial blood stasis, presenting as SEC, and increase the risk of LAA thrombosis (21,22). Studies have shown that BNP can predict the risk of atrial fibrillation (23), thromboembolism (22,(24)(25)(26)(27), and general cardiovascular risk (28)(29)(30). Recent studies have suggested that BNP is not only a predictor of AF, but also an early predictor of cerebral embolism in patients with AF (31).…”
Section: Main Findingsmentioning
confidence: 99%